1990
DOI: 10.1034/j.1399-3054.1990.790111.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preconditioning on electrolyte leakage and lipid composition in black spruce (Picea mariana) stressed with polyethylene glycol

Abstract: T, J. 1990. Effects of preconditioning on electrolyte leakage and lipid composition in black spruce {Picea mariana) stressed with polyethylene glycol. -Physiol. Plant. 79: 71-77.Black spruce {Picea mariana Mill. B. S. P.) rooted cuttings were grown in solution culture and preconditioned by osmotically stressing plants with polyethylene glycol. After relief from preconditioning stress, water relations, membrane leakiness, and the composition of lipids and fatty acids were compared in preconditioned and control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Results were expressed as Membrane Injury Index, the % of total electrolytes (i.e., those that leaked from heat-killed needles). These techniques are described by Zwiazek and Blake (1990) and Odlum and Blake (1996).…”
Section: Morphological and Physiological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were expressed as Membrane Injury Index, the % of total electrolytes (i.e., those that leaked from heat-killed needles). These techniques are described by Zwiazek and Blake (1990) and Odlum and Blake (1996).…”
Section: Morphological and Physiological Measurementsmentioning
confidence: 99%
“…Loss of membrane integrity was suggested by the increase in electrolyte leakage in black spruce under drought (Fan andBlake 1994, Tan andBlake 1993). Severe dehydration causes a decline in sterols, lipids, and their ratio (Zwiazek and Blake 1990). Drought-induced membrane leakage may explain alteration in membrane constituents.…”
mentioning
confidence: 99%
“…The fractions containing sterols were evaporated under nitrogen, the residue dissolved in 0.5 ml pyridine and trimethylsilyl derivatives of sterols were made by adding 0.1 ml trimethylchlorosilane followed by 0.2 ml hexamethyldisilazane (Zwiazek and Blake 1990). Sterols were analyzed using a Hewlett Packard 5890 gas chromatograph equipped with a 30-m-long, 0.25-mm internal diameter DB-5 column (J&W Scientific, Folsom, Calif., USA).…”
Section: Plasma Membrane Isolationmentioning
confidence: 99%
“…Zwiazek and Blake (1990a) found that the osmotic potential of preconditioned black spruce seedlings was lower than that of unconditioned plants before and during subsequent exposure to osmotic stress with polyethylene glycol (PEG (Lawlor, 1970). Zwiazek and Blake (1990b) (Dang et al 1991(Dang et al , 1992. Full recovery of the photosynthetic apparatus after a summer frost may take several weeks (Pharis et al, 1970).…”
Section: Introductionmentioning
confidence: 99%